PROSES PEMBELAJARAN SAINTIFIK PESERTA DIDIK DENGAN SPEKTRUM AUTISME BERBASIS KURIKULUM 2013 DI SEKOLAH DASAR INKLUSIF - Ayu Amborowati, Novitta (Jurnal Pendidikan Khusus, 2017)
ABSTRACT In this descriptive research, the demand to apply curriculum 2013 to all learners required the teachers to be able to prepare learning plan and exact implementation to all learners included learners with autism spectrum in inclusive class. This research purpose was to describe the scientific learning process to learners with autism spectrum based curriculum 2013 in SDN Ketintang II/410 Surabaya. This research used descriptive method with qualitative approach. Based on the data analysis it was obtained that the elements of scientific learning plan for learners had generally been applied by the teachers well. The modification was done to learners with autism spectrum to the material and learning activity. Five learners could follow the scientific learning process in the class while one learner could not yet. The modification was not structurally arranged yet in Individual Learning Program. The implementation had already been done based on the criteria of scientific learning. All learners with autism spectrum needed assistance from GPK and shadow to understand and apply the material. Although the steps of scientific learning were only trying and communicating only two learners could implement them. The learning activity of class IV was implemented in source room with GPK. The assessment of learning result was made exercises with three levels suitable with the learners’ ability. The evaluation was authentically done involving the aspects of attitude, knowledge, and skill to all learners with autism spectrum and the special report was in the form of description report. The hindrance in the implementation was felt by the teachers because the four learners did not master the basic abilities of reading, writing, and counting yet. The characteristics of learners with various autism spectrums made the application of learning elements was not maximally implemented yet. Scientific learning would be more maximal with doing special assistance in the implementation. Keywords: Scientific learning, curriculum 2013